Re-considering Epic and TV - Kozak, Lynn (Sens public, 2021)
This article builds on Kozak’s 2016 monograph, Experiencing Hektor, which argued for using television narrative strategies to re-conceptualise ancient Greek oral epic. Inverting this dynamic, this article looks at how certain features of ancient oral epic can be useful in considering television’s narrative strategies, especially when it comes to repetitive narrative elements, from diverse forms of type-scenes to repeated phrases, character epithets, and longer formulae. The article also foregrounds the roadblocks for such an approach, from confusion over what constitutes a callback in both media, to considering the episode as a narrative unit, as epic episodes are not clearly delineated, and the season-drop continues to challenge the episode as a primary unit of narrative within contemporary television. Finally, the article points to several avenues of narrative analysis for both forms moving forward, urging scholars of Greek epics to think of narrative strategies beyond the constraints of oral composition, and urging television scholars to consider using the close-reading and televisual/textual analysis and data collection that remains central to classics as a discipline, but which are still primarily reserved for fans and popular media critics of television.